Strategies to Overcome Antileishmanial Drugs Unresponsiveness - Shyam Sundar; Anup Singh; Om Prakash Singh (Journal of Tropical Medicine)
In the absence of effective vector control measures and vaccines against leishmaniasis, effective chemotherapy remains the mainstay of treatment. As the armoury of antileishmanial drugs is limited, strategies should be made to target the emergence of drug resistance. The loss of efficacy of antimonials such as sodium stibogluconate in the Indian subcontinent which has been the mainstay of treatment for more than six decades has raised concern to save the other drugs. In the current review, we highlight various steps which could be implemented to halt the increasing unresponsiveness of drugs such as monitoring of therapy in the form of rational dosing and duration of treatment, understanding the mechanism of action of the drugs and drug resistance, identification of markers of resistance, distribution of drugs free of cost, evolution of effective combination therapy and immunotherapy, and proper management of HIV/VL coinfection and post-kala-azar dermal leishmaniasis (PKDL). Strong support from governmental agencies and local communities in the form of education and orientation programmes for feasibility of implementing these strategies and affordability within the context of their health systems is needed in controlling and preventing leishmaniasis.